2010
DOI: 10.1002/humu.21182
|View full text |Cite
|
Sign up to set email alerts
|

A matrilin-3 mutation associated with osteoarthritis does not affect collagen affinity but promotes the formation of wider cartilage collagen fibrils

Abstract: Mutations in matrilin-3 have been associated with common skeletal diseases like osteoarthritis as well as with the rare chondrodysplasias MED and SEMD. We have previously shown that the mutations p.R116W and p.C299S, associated with MED and SEMD, respectively, cause retention of matrilin-3 within the endoplasmic reticulum of primary chondrocytes, while the mutation associated with osteoarthritis, p.T298M, does not hinder secretion. The present study focused on the consequences of the p.T298M mutation on the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Notably, effects of collagen binding/VWA domain containing proteins on collagen assembly were also shown for Matrilin 3 (ref. 38), albeit the observed effects were not as tremendous as shown for PTMP1, suggesting that collagen binding of proteins with tandem-arranged VWA domains could generally provide a so far undetected control mechanism for collagen/matrix assemblies. In the byssus, PTMP1 is predominantly present in the proximal thread section 11 , with its natural targets being most likely PreCol-P or PreCol-NG rather than PreCol-D.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Notably, effects of collagen binding/VWA domain containing proteins on collagen assembly were also shown for Matrilin 3 (ref. 38), albeit the observed effects were not as tremendous as shown for PTMP1, suggesting that collagen binding of proteins with tandem-arranged VWA domains could generally provide a so far undetected control mechanism for collagen/matrix assemblies. In the byssus, PTMP1 is predominantly present in the proximal thread section 11 , with its natural targets being most likely PreCol-P or PreCol-NG rather than PreCol-D.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, the impact of matrix proteins like PTMP1 on collagen fibril formation and assembly is obvious when fibres are artificially drawn from purified PreCol proteins 40,41 , since these fibres were different from the natural byssal threads with respect to size and mechanical characteristics 10 . Concerning the establishment of collagenous materials with new properties, the in vitro function of PTMP1 might inspire material scientists to adjust morphologies and also mechanical features of reconstituted collagen fibres to be used in different applications, for example, in the generation of gradient materials inspired by the mussel byssus 38 . The possibility to recombinantly produce PTMP1 and other byssal proteins 39 opens the gate for a variety of novel bio-inspired materials based on collagen/matrix assemblies, for example, in tissue engineering 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the mild phenotype MATN3 null mice displayed, mutation of a single base, however, could cause MED. Many studies thus presumed that the pathogenic mechanism of MED might be mediated by a dominant negative effect [19,35,36]. Moreover, multiple growth factors, transcription factors and signal proteins of extracellular matrix, such as BMP2 [12], SOX6 [37] and PTHrp [38], have been proved to be associated with BMD.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the osteoarthritis‐associated p.T303M mutation (in mouse p.T298M models) on the structure of matrilin 3 and on the role of matrilin 3 in extracellular matrix assembly were recently analyzed, and the results revealed that this mutation also allowed normal secretion (38), caused only minor changes in protein structure, and did not affect the affinity for collagens. However, a major impact on collagen fibrillogenesis with the formation of wider cartilage collagen fibrils was observed (39). This example confirms that studies of pathogenic changes in rare forms of cartilage degeneration are likely to provide significant insight into the pathogenetic mechanisms of more common forms of the disease, particularly since the sequence of molecular events seems to be largely independent of the factors that first initiated the disease (40).…”
Section: Discussionmentioning
confidence: 99%